Desulfonative photoredox alkylation of N-heteroaryl sulfones – an acid-free approach for substituted heteroarene synthesis. Issue 16 (22nd March 2019) - Wang, Zheng-Jun; Zheng, Shuai; Matsui, Jennifer K.; Lu, Zhipeng; Molander, Gary A.
Abstract : Photoredox-mediated alkylation of heteroaryl sulfones under redox-neutral, acid-free conditions to create drug-like molecules. Abstract : Minisci-type alkylation of electron-deficient heteroarenes has been a pivotal technique for medicinal chemists in the synthesis of drug-like molecules. However, such transformations usually require harsh conditions ( e.g., strong acids, stoichiometric amount of oxidants, elevated temperatures, etc. ). Herein, by utilizing photoredox catalysis, a highly-selective alkylation method using heteroaryl sulfones has been developed that can be carried out under acid-free and redox-neutral conditions. Because of these mild conditions, challenging yet privileged structures, such as monosaccharides and unprotected secondary amines, can be installed.